2010
DOI: 10.1074/jbc.m109.082008
|View full text |Cite
|
Sign up to set email alerts
|

Pannexin1 and Pannexin3 Delivery, Cell Surface Dynamics, and Cytoskeletal Interactions

Abstract: Pannexins (Panx) are a class of integral membrane proteins that have been proposed to exhibit characteristics similar to those of connexin family members. In this study, we utilized Cx43-positive BICR-M1R k cells to stably express Panx1, Panx3, or Panx1-green fluorescent protein (GFP) to assess their trafficking, cell surface dynamics, and interplay with the cytoskeletal network. Expression of a Sar1 dominant negative mutant revealed that endoplasmic reticulum to Golgi transport of Panx1 and Panx3 was mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
107
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 99 publications
(118 citation statements)
references
References 60 publications
(91 reference statements)
8
107
0
Order By: Relevance
“…39 Pannexins do not appear to form the kind of close channel packing that would lead to dense crystalline-like structures, as reported for Cx43. 40 Electron micrographs revealed that Panx1 was localized uniformly at the cell surface in single membranes that were at least 20-50 nm from an apposing cell membrane.…”
Section: Retention and Dynamic Mobility Of Pannexins Within The Plasmmentioning
confidence: 71%
See 4 more Smart Citations
“…39 Pannexins do not appear to form the kind of close channel packing that would lead to dense crystalline-like structures, as reported for Cx43. 40 Electron micrographs revealed that Panx1 was localized uniformly at the cell surface in single membranes that were at least 20-50 nm from an apposing cell membrane.…”
Section: Retention and Dynamic Mobility Of Pannexins Within The Plasmmentioning
confidence: 71%
“…29 Nocodazole-induced disruption of microtubules did not significantly alter the cell surface distribution of Panx1 and Panx3. 39 On the other hand, disruption of microfilaments revealed concomitant intracellular accumulation of Panx1 and Panx3 leaving only a subpopulation at the cell surface. Consistent with this latter finding, Panx1 was found to bind directly to actin, which could suggest that microfilaments act to stabilize the cell surface distribution of Panx1 or even participate in Panx1 delivery or internalization.…”
Section: Retention and Dynamic Mobility Of Pannexins Within The Plasmmentioning
confidence: 99%
See 3 more Smart Citations